Size control of nanoparticles synthesized by pulsed laser ablation in liquids using donut-shaped beams - Altakroury, Abdel Rahman; Gatsa, Oleksandr; Riahi, Farbod; Fu, Zongwen; Flimelová, Miroslava; Samokhvalov, Andrei; Barcikowski, Stephan; Doñate-Buendía, Carlos; Bulgakov, Alexander V.; Gökce, Bilal (Beilstein Journal of Nanotechnology, 2025)
The potential to modify the size distribution of nanoparticles synthesized by pulsed laser ablation in liquids is demonstrated using a donut-shaped laser beam. In experiments on pulsed laser ablation in water of gold, yttrium oxide, and high-entropy alloy targets with both Gaussian and donut-shaped beams, we observed a significant reduction in particle size, narrowing of the size distribution width, and an improvement in sphericity when utilizing the donut-shaped laser beam. We performed time-resolved shadowgraph imaging of the laser-induced cavitation bubble, revealing a toroidal structure that overruns the ring-shaped ablation site, compared to the quasi-hemispherical bubble covering the ablation spot produced by the Gaussian beam. Based on this pioneering study, further investigation with higher temporal and spatial resolution are warranted.
Keywords: beam shaping; cavitation bubble; donut beam; gold nanoparticles; high-entropy alloy nanoparticles; nanoparticle size analysis; yttrium oxide nanoparticles